Carbazole‐Linked 1, 2, 3‐Triazoles: In Vitro β‐Glucuronidase Inhibitory Potential, Kinetics, and Molecular Docking Studies. Issue 20 (28th May 2019) - Shaikh, Nimra Naveed; Iqbal, Shazia; Syed, Naima; Khan, Maria A.; Moin, Syed Tarique; Choudhary, Muhammad Iqbal; Basha, Fatima Z.
Abstract: β‐Glucuronidase enzyme is a tetrameric glycoprotein present in microsomes and lysosomes of many organs, and body fluids. Over‐expression of this enzyme is observed in several melanomas and carcinomas. Therefore, it has been identified as a target for the treatment of several pathological conditions. In this regard, carbazole linked 1, 2, 3‐triazoles (1–27 ) were synthesized according to our previous report, and evaluated for their in vitro β‐glucuronidase inhibitory activities. Compounds 7–10, 17–18, 20, and 22–27 showed potent activities with IC50 values between 0.55–32.5 μM, as compared to the standard, D‐saccharic acid 1, 4‐lactone (IC50 =45.75 ± 2.16 μM). All active compounds were found to be non‐cytotoxic against mouse fibroblast 3T3 cell line. Compounds 20, 22, 23, 25, 26, and 27 were subjected to enzyme kinetic studies for the determination of their modes of inhibition, and dissociation constants Ki. Compounds 23, 25, and 26 were also studied for their mode of inhibition by using molecular docking methods. Abstract : A series of carbazole linked 1H ‐1, 2, 3‐triazoles was subjected to in vitro inhibitory activity against the β‐glucuronidase enzyme that showed IC50 values between 0.55 and 32.5 μM that was more potent that the standard, D‐saccharic acid 1, 4‐lactone. Selected compounds were also subjected to kinetic and molecular docking studies for the determination of their modes of inhibition.